2008
DOI: 10.1093/jjco/hyn064
|View full text |Cite
|
Sign up to set email alerts
|

Trend in Incidence of Adenocarcinoma of the Esophagus in Japan, 1993-2001

Abstract: No dramatic increase in adenocarcinoma has occurred, and absolute incidence remains low in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 19 publications
3
70
3
3
Order By: Relevance
“…While we found a ratio of 2/1 for SCC/AC and SCC has majority of tumors in some other reports too (from Japan (26/1) (Shibata et al, 2008) and Iran and AC are equal and even a higher rate of AC in recent decades has been recorded (Kumar, 2007;Bennett and Goldblum, 2009). Several line of studies have shown a decrease in proportion of SCC in recent decades (Devesa et al, 1998;Botterweck et al, 2000;Makhdoomi et al, 2005;Aragones et al, 2010;Gopala Krishnappa et al, 2013) but the severity varied between different countries (Triboulet and Mariette, 2008).…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gascontrasting
confidence: 53%
See 1 more Smart Citation
“…While we found a ratio of 2/1 for SCC/AC and SCC has majority of tumors in some other reports too (from Japan (26/1) (Shibata et al, 2008) and Iran and AC are equal and even a higher rate of AC in recent decades has been recorded (Kumar, 2007;Bennett and Goldblum, 2009). Several line of studies have shown a decrease in proportion of SCC in recent decades (Devesa et al, 1998;Botterweck et al, 2000;Makhdoomi et al, 2005;Aragones et al, 2010;Gopala Krishnappa et al, 2013) but the severity varied between different countries (Triboulet and Mariette, 2008).…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gascontrasting
confidence: 53%
“…Several line of studies have shown a decrease in proportion of SCC in recent decades (Devesa et al, 1998;Botterweck et al, 2000;Makhdoomi et al, 2005;Aragones et al, 2010;Gopala Krishnappa et al, 2013) but the severity varied between different countries (Triboulet and Mariette, 2008). In Japan there wasn't any change (Shibata et al, 2008). Some parts of north of Iran (Golestan province) located in the worldwide belt of esophageal cancer.…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gasmentioning
confidence: 99%
“…Shibata et al [31] reported on trends in the incidence of adenocarcinoma of the esophagus in Japan, and indicated that no increase in the incidence of these tumors was observed. The proportion of AEG among upper gastrointestinal (GI) tract cancers at Kanagawa Cancer Center was analyzed and the incidence had not changed in 20 years (Table 1).…”
Section: Incidence Of Aeg In Eastern Countriesmentioning
confidence: 99%
“…Mortality decreased over the six years in both genders, although it remained high in the Yanting area (Song et al, 2012). In Japan, estimated average annual percentage change for adenocarcinomas was 4.7% (95% confidence interval: 0.7, 8.9) in men and 6.0% (2.4, 9.8) in women Japan SCC slight increase (Shibata et al, 2008). Oesophageal adenocarcinoma is increasing in NSW, possible contributing factors include increasing obesity (Stavrou et al, 2009).…”
Section: Oesophagealmentioning
confidence: 95%